1999
DOI: 10.1101/gad.13.12.1561
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo-oxygenase-2-derived prostacyclin mediates embryo implantation in the mouse via PPARdelta

Abstract: We have demonstrated previously that cyclo-oxygenase-2 (COX2), the rate-limiting enzyme in the biosynthesis of prostaglandins (PGs), is essential for blastocyst implantation and decidualization. However, the candidate PG(s) that participates in these processes and the mechanism of its action remain undefined. Using COX2-deficient mice and multiple approaches, we demonstrate herein that COX2-derived prostacyclin (PGI 2 ) is the primary PG that is essential for implantation and decidualization. Several lines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
369
4
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 560 publications
(394 citation statements)
references
References 76 publications
19
369
4
2
Order By: Relevance
“…It was demonstrated that PPARg and PPARd/b are key mediators of normal blastocyst implantation and elongation in early gestation and it has been shown that COX2 mediates embryo implantation in the mouse via PPARd/b (Lim et al, 1999;Huang, 2008). Taken altogether, these results indicate a link between the type of omega (3 v. 6) FA present in the diet, the type of prostaglandins synthesised (series 2 v. 3), and the expression of genes involved in reproduction.…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 88%
See 1 more Smart Citation
“…It was demonstrated that PPARg and PPARd/b are key mediators of normal blastocyst implantation and elongation in early gestation and it has been shown that COX2 mediates embryo implantation in the mouse via PPARd/b (Lim et al, 1999;Huang, 2008). Taken altogether, these results indicate a link between the type of omega (3 v. 6) FA present in the diet, the type of prostaglandins synthesised (series 2 v. 3), and the expression of genes involved in reproduction.…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 88%
“…Therefore, strategies to further inhibit secretion of series 2 prostaglandins may result in increased embryonic survival and pregnancy rates. The production of endometrial series 2 prostaglandins is mainly governed by the rate-limiting enzyme cyclooxygenase (COX)-2, which mediates embryo implantation in the mouse (Lim et al, 1999;Huang, 2008). The most potent COX-2 inhibitor is an omega 3 FA, eicosapentanoic acid (Ringbom et al, 2001).…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 99%
“…Alternatively, the perinuclear PGE 2 (or possibly other unknown metabolites) produced by COX-2/mPGES-1 may act on certain nuclear receptors that in turn promote cell growth. Indeed, several eicosanoids have been shown to stimulate the peroxisome proliferator-activated receptor family of nuclear receptors (43,44). Nonetheless, different sensitivity of PGE 2 production by HCA-7 cells to COX-2 and mPGES-1 inhibitors and mPGES-1 antisense oligonucleotide strongly argues that this cell line may contain an alternative COX-2-dependent PGE 2 -biosynthetic route that involves other PGES enzyme(s).…”
Section: Mpges-1 and Tumorigenesismentioning
confidence: 98%
“…It is also unknown whether or not Ptgis is also expressed at the implantation site of hamsters as reported previously in mice (17). One way to address these concerns is by co-localization of Ptgs2 and PGE 2 -or PGI 2 -synthesizing enzymes at the same location of implantation sites.…”
Section: Fig 5 Peri-implantation (Daysmentioning
confidence: 99%
“…PGE 2 may also have immunomodulatory roles at the implantation site (15). Recently, it has been demonstrated in the mouse that uterine PGE 2 and PGI 2 are important for ovulation and initiation of implantation, respectively (16,17). In contrast, Kennedy (18) showed that in the rat PGE 2 but not PGI 2 is a key mediator of increased vascular permeability at the implantation site.…”
mentioning
confidence: 99%